Kajian Kebijakan Kurikulum Indonesia 1947-2013 - Bayu Ananto Wibowo (Journal on Education, 2021)
This study aims to determine the direction of policies and goals of Indonesian education from 1947 to 2013 through quality control of education, namely the curriculum. This study uses the method of literature review. The steps of this research are to collect literature sources that support the research, read and analyze the literature, then process the research material into a literature review. The results of this research are reports or information that can be sources or references used for various purposes in the world of education.